Advances in adjuvant therapy for operable N2 non-small cell lung cancer: a narrative review - Liu, Lei; Mao, Yilong; Guo, Leilei; Li, Chencong; Wang, Yiqian (Frontiers in Oncology, 2025)
Non-small cell lung cancer (NSCLC) is still the disease with the highest incidence rate among malignant tumors, in which NSCLC under N2 stage has obvious survival differences among different patients due to its high heterogeneity. For NSCLC under this stage, the current treatment options are: preoperative neoadjuvant therapy, surgical treatment, postoperative adjuvant chemotherapy, postoperative adjuvant radiotherapy (PORT), Postoperative adjuvant targeted therapy and postoperative adjuvant immunotherapy. Whether postoperative adjuvant radiotherapy is routinely administered to patients with pN2 remains controversial in clinical application. Meanwhile, the booming development of adjuvant targeted therapy and adjuvant immunotherapy also provides newer therapeutic options for the prognosis of postoperative pN2 stage NSCLC, and some new markers will guide the adaptive application of immune drugs in the future. This article analyzes the current stage of therapeutic advances in operable stage N2 non-small cell lung cancer, and discusses in detail in this article the therapeutic controversy of postoperative adjuvant radiotherapy in pN2 stage non-small cell lung cancer, so as to explore a more reasonable treatment mode for future patients with stage N2 non-small cell lung cancer.